Processo criativo em dança: o corpo-novelo - Macedo, Aline Rosa (2012)
This paper presents a glimpse into the creative process of the contemporary dance performance \"Des(fio)\", which I experienced as a performer/creator, and where I aimed to discover the ways and procedures taken to reach the corporal state \"corponovelo.\" In order to obtain this, the work of creation was based on experiences of eutony that aimed to develop awareness and relaxation of muscle tone. For this research, I seek refuge in Jorge Larrosa´s concept of experience and in Narciso Telles´s view on the use of experience as a methodological approach. At the end, it was possible to notice that this personal and artistic search modified and broadened my vision of dance, resulting in a change of aesthetic and ethical positioning on my part.